Generalized coherent states and extremal positive operator valued measures - Heinosaari T; Pellonpaa JP (IOP PUBLISHING LTD, 2022)
We present a correspondence between positive operator valued measures (POVMs) and sets of generalized coherent states. POVMs describe quantum observables and, similar to quantum states, quantum observables can also be mixed. We show how the formalism of generalized coherent states leads to a useful characterization of extremal POVMs. We prove that covariant phase-space observables related to squeezed states are extremal, while those related to number states are not extremal.